SHOTGUN METAGENOMIC ANALYSIS OF ASYMPTOMATIC AND MILD SYMPTOMATIC FROM NASOPHARYNGEAL SWAB OF COVID-19 PATIENTS - Vito Sebastian, Eugene
The COVID-19 pandemic is caused by Severe Acute Respiratory Syndrome Coronavirus 2 and causes common symptoms such as fever, shortness of breath, cough, and fatigue. Previous research showed that more than 50% of severe COVID-19 patients died from bacterial coinfection caused by microbial community dysbiosis due to viral infection through complications such as pneumonia. However, studies on dysbiosis in COVID-19 patients have not been widely carried out in Indonesia. Therefore, the purpose of this study is to determine the bacterial community in asymptomatic COVID-19 patients and patients with mild symptoms in Indonesia, especially in West Java. Nasopharyngeal swab samples from asymptomatic and mild symptomatic patients were recruited from Hasan Sadikin Hospital and Labkes Jabar. This study used four samples of asymptomatic patients (A1, A2, A3, and A4) and five samples of patients with mild symptoms (S6, S7, S13, S14, and S18). Bacterial community analysis was carried out using a shotgun metagenomic approach. Samples were prepared using the Ribo-Zero-Plus library preparation method and then sequence readings were performed with Illumina NextSeq 550. The readings were then mapped using Kraken 2 with the minikraken_8GB_20200312 database. Statistical analysis and data visualization were performed using R Studio and Excel programs. Microbiome diversity in the sample was determined using alpha diversity analysis, while the microbiome diversity between samples was calculated using beta diversity analysis using Principal Component Analysis. The relative abundance of bacteria in the mildly symptomatic group to the asymptomatic group was determined using DESeq2 analysis. Furthermore, the species that were significantly increased in the DESeq2 analysis were further analyzed by pheatmap. The results of the analysis of alpha diversity showed that the level of diversity was relatively lower in the group with mild symptoms when compared to the group without symptoms, while the results of the analysis of beta diversity showed differences in the diversity profile of the microbiome in the group with mild symptoms when compared to the group without symptoms. Volcano plot results from DESeq2 show a higher abundance of 48 species in mildly symptomatic samples when compared to asymptomatic patients. The pheatmap results showed a higher abundance of opportunistic bacterial species, Streptococcus pneumoniae, S. mitis, and Rothia mucilaginosa, as well as commensal bacteria, Actinomyces naeslundii, Gemella haemolysans, S. gordonii, S. sanguinis, and S. cristatus in samples with mild symptoms, especially in samples S14 and S18, when compared to asymptomatic samples. From this study, it can be concluded that there are differences in the profile of bacterial abundance in the nasopharyngeal swab sample between the group of COVID-19 patients with mild symptoms and the group of asymptomatic patients. In the future, this research can be used for the purposes of prognosis, development of diagnostic kits, and selection of appropriate drugs to prevent bacterial coinfection in COVID-19 patients.